2007
DOI: 10.1159/000111715
|View full text |Cite
|
Sign up to set email alerts
|

Role of <sup>18</sup>F-Fluorodeoxyglucose Positron Emission Tomography in Detecting Extrahepatic Metastasis in Pretreatment Staging of Hepatocellular Carcinoma

Abstract: Objectives:18F-fluorodeoxyglucose positron emission tomography (FDG-PET) is useful for differentiating benign from malignant lesions, evaluating tumor stage, monitoring the response to therapy and detecting tumor recurrence in a variety of malignancies. Nevertheless, its use in patients with hepatocellular carcinoma (HCC) is still uncertain. We evaluated whether FDG-PET has a role in detecting extrahepatic metastasis in pretreatment tumor staging of HCC and the characteristics of patients with extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 31 publications
(19 reference statements)
2
46
0
1
Order By: Relevance
“…Increased TSUVmax/MSUVmean ratio also correlated well with higher stages of disease in both the TNM and BCLC staging systems. These findings are compatible with other studies using tumor SUV or the tumor to non-tumor SUV ratio as parameters to predict the tumor characteristics (24,34,35).…”
Section: F-fdg Pet Ct In Hccsupporting
confidence: 92%
“…Increased TSUVmax/MSUVmean ratio also correlated well with higher stages of disease in both the TNM and BCLC staging systems. These findings are compatible with other studies using tumor SUV or the tumor to non-tumor SUV ratio as parameters to predict the tumor characteristics (24,34,35).…”
Section: F-fdg Pet Ct In Hccsupporting
confidence: 92%
“…The role of positron emission tomography (PET) in the diagnostic and staging evaluation of HCC still remains uncertain. Several studies have suggested a role for [ 18 F]fluorodeoxyglucose (FDG)-PET scanning for the detection of primary HCCs, tumor staging, assessing response to therapy, and for predicting prognosis [231][232][233]. HCCs accumulate FDG to varying degrees (only 55-65% of tumors give a positive result by PET scanning), limiting the sensitivity of PET for primary tumors [234,235].…”
Section: Other Imaging Modalitiesmentioning
confidence: 99%
“…HCCs accumulate FDG to varying degrees (only 55-65% of tumors give a positive result by PET scanning), limiting the sensitivity of PET for primary tumors [234,235]. However, FDG-PET seems to be a useful imaging modality for identifying extrahepatic metastases, although sensitivity is limited for lesions 1 cm or smaller [231,236]. …”
Section: Other Imaging Modalitiesmentioning
confidence: 99%
“…The ability of PET to detect HCC in the liver was found to be less effective than that of contrast enhanced CT (14). On the other hand, yoon et al (15) and Sugiyama et al (16) reported that PET is useful for the screening of extrahepatic metastasis from HCC. Recently, the usefulness of FDG-PET for predicting HCC recurrence following liver transplantation was proposed (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Full body scanning with PET/CT is useful for the screening of extrahepatic metastasis and staging in patients with large HCC (15). An FDG-PET/CT examination is non-invasive and useful for predicting the malignant pathological potential of HCC before resection without the need for a biopsy.…”
Section: Discussionmentioning
confidence: 99%